ENHANCES CONTROL OF ENVIRONMENTAL FEASIBILITY SECURITY IN MEDAN CITY DEVELOPMENT IN LIQUID WASTE BIODIGESTER TOFU FACTORY - Asmara Sari Nasution; Efi Said Ali (Sean Institute, 2022)
The impact of processing the tofu industry is liquid waste which mainly causes problems. Tofu liquid waste can be used as biogas. For this reason, it is necessary to study a feasibility analysis for constructing a biodigester from a technical, economic, and environmental perspective. The engineering work process in technical analysis determines the type of digester and the appropriate and efficient placement obtained from operational costs, land area, and production capacity. The technical analysis survey found that the type of reactor installation was chosen was the modified Cover Lagoon Anaerobic Reactor (Colar) with a portable model with a capacity of 200 liters. The economic analysis study is used to determine the feasibility of developing a Biodigester in determining the budget details and obtaining the estimated cost of Rp. 2,301,000, - and investment in the next five years with parameters Net Present Value (NPV) = Rp. 7.512.000,- (positive value), Probability Index (PI) = 3.2 1 in the investment period, Internal Rate Of Return (IRR) at the generally accepted interest rate, the NPV is positive, and there is no IRR and Payback Period (PP) = 1.3 Years (≤ investment period of 5 years). Environmental feasibility analysis shows that the outer biodigester is safe and has a slightly pungent odor and reduced tofu factory liquid waste. Handling from the exterior involves a particular route to closed drainage or pipe to a final disposal site or a closed septic tank.